Xenophanes DK 21 B 18, a Testimony of the Rising Philosophy - Galgano, Nicola Stefano (Peitho. Examina Antiqua, 2024)
Greek seafaring between the 10th and 6th centuries BCE gave rise to a technical culture centered around navigation, commerce, and international cultural exchange. The Greeks were not a unified nation in the modern sense, confined to a territory centralized in Attica or the Peloponnese. Instead, they were a collection of independent city-states (poleis) spread across the Mediterranean, from the Iberian Peninsula to the Black Sea. The intense commercial relationships among these Greek settlements and with other peoples wove a Mediterranean cultural web that fostered a genuine spirit of intercultural exchange, leading to a new cultural synthesis that gave the Greeks – and the world to this day – an extraordinary drive for originality. This technical culture, which Rossetti calls the “cultura dell’attendibilità,” was based on observation, objectivity, and rationality. Without these principles, and relying solely on myth, seafaring could never have flourished. This shift away from myths to a new culture is testified by Xenophanes, who, in DK B 18 (LM D53), contrasts the ancient method of gaining knowledge through communication with the gods with a new method of research that in time yields better results.